2014
DOI: 10.1039/c4tb00372a
|View full text |Cite
|
Sign up to set email alerts
|

Ti–SrO metal matrix composites for bone implant materials

Abstract: Titanium–strontia (Ti–SrO) metal matrix composites (MMCs) with 1, 3 and 5% (weight ratio) of SrO have been fabricated through the powder metallurgy method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…5 . It can be seen that the compressive yield strengths of the titanium matrix composites with 2%, 3% and 4% of Nb 2 O 5 additions are 1245 ± 52, 1310 ± 54 and 1409 ± 58 MPa, respectively, which are higher than that of pure titanium fabricated by powder metallurgy (1046 ± 50 MPa) [16] . The compressive yield strength of the Ti-Nb 2 O 5 composites increased with increasing Nb 2 O 5 addition.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…5 . It can be seen that the compressive yield strengths of the titanium matrix composites with 2%, 3% and 4% of Nb 2 O 5 additions are 1245 ± 52, 1310 ± 54 and 1409 ± 58 MPa, respectively, which are higher than that of pure titanium fabricated by powder metallurgy (1046 ± 50 MPa) [16] . The compressive yield strength of the Ti-Nb 2 O 5 composites increased with increasing Nb 2 O 5 addition.…”
Section: Resultsmentioning
confidence: 87%
“…The titanium alloy coated with Nb 2 O 5 by using a sol–gel technique can significantly improve its biocompatibility, bioactivity and corrosion resistance [14] , [15] . It has been reported that particulate-reinforced titanium metal matrix composites using metal oxides as reinforcements, such as TiO 2 , SiO 2 , ZrO 2 and SrO, show promising mechanical properties and excellent biocompatibility for orthopedic implant materials [16] , [17] , [18] . In this study, to simultaneously achieve high strength and excellent biocompatibility for load-bearing applications, we attempt reinforcing titanium metal matrix with Nb 2 O 5 particulate to fabricate a Ti-Nb 2 O 5 composite for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a mitigation measure, the development of Ti based composites reinforced with biocompatible and refractory materials have been advanced [14]. The state-of-the-art shows that several metallic oxides (TiO 2 , SrO 2 , ZrO 2 ), phosphates, and hydroxyapatite have been investigated for potential use as reinforcement in Ti based composites for load bearing orthopedic applications [15][16][17][18][19]. The consideration of niobium pentoxide (Nb 2 O 5 ) has been the subject of recent interest [20].…”
Section: Introductionmentioning
confidence: 99%